Perusakan Komponen Kendaraan Rental: Wanprestasi Dalam Kontrak Sewa Kendaraan - I Putu Agus Gilang Sedana Putra; A.A. Gede Duwira Hadi Santosa (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2024)
A stipulation born between two or more parties that is legally guaranteed and creates specific rights and obligations for each individual is the definition of a contract. In the law of obligations, a contract is considered a fundamental instrument that allows individuals or entities to manage their relationships with each other. However, in practice, breaches or non-compliances with what has been agreed upon, known as